Perancangan Website Pada Kantor Camat Mulak Ulu Kabupaten Lahat Dengan Metode Waterfall Menggunakan Framework Laravel - Fernando gilang Putra Ramadhan; Marlindawati Marlindawati (Jurnal Nasional Ilmu Komputer, 2022)
The Mulak Ulu Sub-District Office of Lahat Regency provides public services to the community as the executor of regional techniques that act as Regency/City regional apparatus, regarding population data. At the Mulak Ulu sub-district office, Lahat district has problems in carrying out public services and conventional information dissemination has an impact that can reduce the accountability and accountability of the Mulak Ulu sub-district office in Lahat district. The research method used in this study is a sequential method. systematic process in the process will be more effective and efficient in designing a website-based system using the Laravel Framework which is a PHP framework composed of several integrated plugins